Methionyl-tRNA synthetase from Bacillus stearothermophilus: structural and functional identities with the Escherichia coli enzyme. - Mechulam, Y (1991)
The metS gene encoding homodimeric methionyl-tRNA synthetase from Bacillus stearothermophilus has been cloned and a 2880 base pair sequence solved. Comparison of the deduced enzyme protomer sequence (Mr 74,355) with that of the E. coli methionyl-tRNA synthetase protomer (Mr 76,124) revealed a relatively low level (32%) of identities, although both enzymes have very similar biochemical properties (Kalogerakos, T., Dessen, P., Fayat, G. and Blanquet, S. (1980) Biochemistry 19, 3712-3723). However, all the sequence patterns whose functional significance have been probed in the case of the E. coli enzyme are found in the thermostable enzyme sequence. In particular, a stretch of 16 amino acids corresponding to the CAU anticodon binding site in the E. coli synthetase structure is highly conserved in the metS sequence. The metS product could be expressed in E. coli and purified. It showed structure-function relationships identical to those of the enzyme extracted from B. stearothermophilus cells. In particular, the patterns of mild proteolysis were the same. Subtilisin converted the native dimer into a fully active monomeric species (62 kDa), while trypsin digestion yielded an inactive form because of an additional cleavage of the 62 kDa polypeptide into two subfragments capable however of remaining firmly associated. The subtilisin cleavage site was mapped on the enzyme polypeptide, and a gene encoding the active monomer was constructed and expressed in E. coli. Finally, trypsin attack was demonstrated to cleave a peptidic bond within the KMSKS sequence common to E. coli and B. stearothermophilus methionyl-tRNA synthetases. This sequence has been shown, in the case of the E. coli enzyme, to have an essential role for the catalysis of methionyl-adenylate formation.